2020
DOI: 10.1038/s41467-020-19547-6
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological targeting of MCL-1 promotes mitophagy and improves disease pathologies in an Alzheimer’s disease mouse model

Abstract: There is increasing evidence that inducing neuronal mitophagy can be used as a therapeutic intervention for Alzheimer’s disease. Here, we screen a library of 2024 FDA-approved drugs or drug candidates, revealing UMI-77 as an unexpected mitophagy activator. UMI-77 is an established BH3-mimetic for MCL-1 and was developed to induce apoptosis in cancer cells. We found that at sub-lethal doses, UMI-77 potently induces mitophagy, independent of apoptosis. Our mechanistic studies discovered that MCL-1 is a mitophagy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
93
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 132 publications
(99 citation statements)
references
References 60 publications
5
93
0
1
Order By: Relevance
“…In recent studies, we developed a high-throughput method for screening mitophagy inducers [ 1 ]. We used mt-Keima protein, which was previously established as a robust sensor of mitophagy, to construct a stable expression cell line.…”
mentioning
confidence: 99%
“…In recent studies, we developed a high-throughput method for screening mitophagy inducers [ 1 ]. We used mt-Keima protein, which was previously established as a robust sensor of mitophagy, to construct a stable expression cell line.…”
mentioning
confidence: 99%
“…This reserve of AMBRA1 is released from BCL-2 when autophagy is induced, allowing it to bind to BECLIN1 and initiate the formation of the phagophore at the mitochondrion [ 84 , 85 ]. Cen et al report that MCL-1, an important anti-apoptotic protein, is a mitophagy receptor that can be targeted to induce mitophagy and identify MCL-1 as a drug target for therapeutic intervention in Alzheimer's disease [ 86 ].…”
Section: Mitophagymentioning
confidence: 99%
“…MCL-1 is another vital anti-apoptosis protein, identified recently as a novel mitophagy receptor. This protein triggers mitophagy in an Alzheimer's disease mouse model through the action of UMI-77 [49].…”
Section: Ubiquitin-independent Mitophagy In Mammalian Cellsmentioning
confidence: 99%
“…Recent research has reported compounds including beta-Asarone and UMI-77 that help improve the learning and memory of AD mice as well as ameliorate disease pathologies by promoting mitophagy [49,130]. Another two compounds (nicotinamide riboside and urolithin A) are also reported to induce mitophagy.…”
Section: Alzheimer's Diseasementioning
confidence: 99%